On obtaining optical solitons of the perturbed cubic-quartic model having the Kudryashov's law of refractive index - Cinar, Melih; Cakicioglu, Hasan; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa (SPRINGER, 2024)
This article delves into the study of the perturbed cubic-quartic Kudryashov's equation having the Kudryashov's law of refractive index which is recently introduced to the literature. Utilizing the extended rational sine/cosine and sinh/cosh methods, optical solutions such as dark, periodic, and singular are successfully extracted. The two- and three-dimensional plots of these solutions are demonstrated. Besides, the behavior of solitons and the effects of parameters on wave properties are vividly illustrated to explore how the model's parameters influence these solutions. The findings herein can serve as a positive contribution to future research in nonlinear optics, while the methodology employed can be leveraged for similar nonlinear models in real life.
Keywords: Kudryashov's law of refractive index; Effects of parameters; Optical solutions; The extended rational sine/cosine and sinh/cosh methods; NONLINEAR SCHRODINGER; EQUATION; Engineering; Physics; Optics